Acknowledgment of divorce from the book of branches of jurisprudence by Imam Al-Sharwani in his commentary on Tuhfat Al-Muhtaj (a comparative study) - Bashir Muhammad Ibrahim; Saleh Qaddouri Sabah (Islamic Sciences Journal, 2025)
This study summarizes the vocabulary related to the branches of jurisprudence pertaining to the approval of divorce. It then examines the opinions and evidence of jurists regarding the exception of one wife from the four divorces, the suspension of divorce by will, and the occurrence of divorce based on doubt regarding the oath of divorce and Allah Almighty. Allah Almighty has made the true Islam the final of these divine religions. Islam is distinguished by its organization of the affairs and lives of individuals. These principles and rules are generally presented without delving into specific aspects, which has given Islamic legislation the ability to adapt to realities and developments in various areas of life, regardless of time, place, and circumstances. Thanks to this characteristic, Islam has been able to maintain its strength and validity in all eras and places.